Pengaruh Penambahan Serbuk Ban Bekas Terhadap Parameter Marshall Pada Aspal Beton Campuran Panas Lapis Aus AC-WC - M, Radiks Gilang; A, Zaaim; Warsiti, Warsiti; Kusdiyono, Kusdiyono (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2018)
The performance of the mixture characteristic of flexible pavement construction on the laston AC-WC mixture as a surface layer (wear layer) with the addition of used tire powder, is expected to be an alternative material to increase the quality and durability. This research was conducted to analyze the characteristics of the Laston AC-WC mixture with the use of polymeric materials in the form of used tire powder. Addition of added ingredients such as used tire powder to the asphalt mixture can provide better resistance to high temperatures and loads, compared to asphalt without added material added. The research objective was to add used tire powder to the optimum asphalt content of asphalt variation (0%, 5%, 10%, 15%) under standard conditions with 2x75 collisions and refusal conditions or balancing with 2x400 collisions. The results showed that the KAO used (6.0%) which affects the value of Density, VMA, VFA, VIM, VIM Refusal density, Marshall Stability, Flow, MQ, and Marshall Time Stability. AC-WC mixture with four variations in the addition of tire powder (0%, 5%, 10%, 15%).Kata kunci : laston AC-WC, parameter marshall, serbuk ban bekas